The Future is Asian : global order in the twenty-first century - Khanna, Parag (London : Weidenfeld & Nicolson, 2019)
Leading global strategist Parag Khanna explains how Asia is reshaping the entire planet and setting a new template for our collective future. Five billion people, two-thirds of the world's mega-cities, one-third of the global economy, two-thirds of global economic growth, thirty of the Fortune 100, six of the ten largest banks, eight of the ten largest armies, five nuclear powers, massive technological innovation, the newest crop of top-ranked universities. Asia is also the world's most ethnically, linguistically and culturally diverse region of the planet, eluding any remotely meaningful generalization beyond the geographic label itself. Even for Asians, Asia is dizzying to navigate. Whether you gauge by demography, geography, economy or any other metric, Asia is already the present and it is certainly the future. It is for this reason that we cannot afford to continue to get Asia so wrong.
Includes Bibliographical References and Index.
Keywords: Asia Economic conditions; Asia Foreign relations; Asia Politics and government